IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE THE LEARNING OUTCOMES OF GRADE IV STUDENTS IN THE SUBJECT OF SCIENCE AT SDK SAWU - Kaka, Pelipus Wungo; Awe, Ermelinda Yosefa; Lawe, Yosefina Uge; Pio, Maria Oktaviani (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The objective of this study is to determine the learning outcomes in the IPAS subject for Grade IV students at SDK Sawu through the implementation of the Problem Based Learning model. This research is a Classroom Action Research (CAR) using the Kemmis and Mc. Taggart design, which consists of four stages: planning, action, observation, and reflection. After the observation stage, reflection is carried out to evaluate the strengths and weaknesses of the learning process and to plan improvements for the next cycle. This reflection serves as the basis for refining the actions in the following cycle. The subjects of this study are 16 fourth-grade students at SDK Sawu, consisting of 10 female students and 6 male students. Data collection techniques include observation, learning outcome tests, and documentation. The instruments used are observation sheets for teacher and student activities as well as evaluation test items. Data were analyzed using descriptive quantitative analysis by calculating the average scores and the percentage of class mastery. Based on the data analysis in Cycle I, the average learning result was 67.5%, with a classical completeness percentage of 37.5%, which falls under the